Two-dimensional porous nickel oxalate thin sheets constructed by ultrathin nanosheets as electrode materials for high-performance aqueous supercapacitors. Issue 17 (14th April 2020) - Zhao, Chenglan; Jiang, Yuqian; Liang, Shunfei; Gao, Fang; Xie, Li; Chen, Lingyun
Abstract : 2D porous nickel oxalate thin sheets constructed by ultrathin nanosheets were first synthesized by using a simple hydrothermal method. The resulting porous thin sheets exhibited superior supercapacitor performance. Abstract : Two-dimensional (2D) materials have attracted extensive interest due to their unique structure-induced properties and potential applications in energy conversion and storage. In this work, large-scale 2D porous nickel oxalate (CQU-Chen-Ni-OA-1) thin sheets constructed by ultrathin nanosheets were first synthesized via a simple hydrothermal method using nickel nitrate (Ni(NO3 )2 ·6H2 O) and oxalic acid (OA) as raw materials. The as-synthesized Ni-OA porous thin sheets feature high specific surface areas of up to 136.52, 73.65 and 54.37 m 2 g −1 and abundant hierarchical short pores, which provide a large number of active sites for ion adsorption, supply plentiful channels for fast ion transport and boost electrical conductivity. As electrodes for supercapacitors, the Ni-OA thin sheets manifest high specific capacity values of up to 1134.024 C g −1 (specific capacitance of 2835.06 F g −1 ) at 1.0 A g −1, and even 134.48 C g −1 (336.20 F g −1 ) at 10 A g −1, and excellent cycle stability, with 94.3% of the initial capacitance retained after 5000 cycles in 6 mol L −1 KOH aqueous electrolyte. To further investigate the practical applications of the as-synthesized Ni-OA thin sheets, an aqueous asymmetric supercapacitor (Ni-OA thin sheets (+)//active carbon (AC) (−)) was assembled that can gain a high energy density of 35.7 W h kg −1 at a power density of 900 W kg −1 and was able to maintain 92.5% of its initial specific capacitance after 10 000 cycles. The excellent electrochemical performance of the Ni-OA thin sheets could be ascribed to their unique 2D/3D structure composed of interconnected ultrathin nanosheets, which facilitated electron transportation and ion penetration. The present synthetic route provides a facile method for large-scale production of Ni-OA thin sheets for use in high-performance energy storage devices.